Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Certainly! Let's break this down step-by-step to find [tex]\( g(h(t)) \)[/tex].
### Step 1: Understand the Functions
Given the functions:
[tex]\[ g(t) = 2t + 3 \][/tex]
[tex]\[ h(t) = 3t - 4 \][/tex]
### Step 2: Substitute [tex]\( h(t) \)[/tex] into [tex]\( g \)[/tex]
We need to find [tex]\( g(h(t)) \)[/tex]. This means we will substitute the function [tex]\( h(t) \)[/tex] into the function [tex]\( g(t) \)[/tex].
### Step 3: Substitute [tex]\( h(t) \)[/tex] into [tex]\( g(t) \)[/tex]
First, we rewrite [tex]\( g(t) \)[/tex] so that it accepts [tex]\( h(t) \)[/tex]:
[tex]\[ g(t) = 2t + 3 \][/tex]
When substituting [tex]\( h(t) \)[/tex], we replace [tex]\( t \)[/tex] in [tex]\( g(t) \)[/tex] with [tex]\( h(t) \)[/tex]:
[tex]\[ g(h(t)) = g(3t - 4) \][/tex]
### Step 4: Evaluate [tex]\( g(3t - 4) \)[/tex]
Now, substitute [tex]\( 3t - 4 \)[/tex] wherever there is a [tex]\( t \)[/tex] in the function [tex]\( g(t) \)[/tex]:
[tex]\[ g(3t - 4) = 2(3t - 4) + 3 \][/tex]
### Step 5: Simplify the Expression
Next, we simplify the expression step-by-step:
[tex]\[ 2(3t - 4) + 3 \][/tex]
[tex]\[ = 2 \cdot 3t - 2 \cdot 4 + 3 \][/tex]
[tex]\[ = 6t - 8 + 3 \][/tex]
[tex]\[ = 6t - 5 \][/tex]
So, [tex]\( g(h(t)) = 6t - 5 \)[/tex].
### Final Answer:
To find the specific value of [tex]\( g(h(t)) \)[/tex] for a particular [tex]\( t \)[/tex], you would substitute the value of [tex]\( t \)[/tex] into [tex]\( 6t - 5 \)[/tex]. For example, if [tex]\( t = 0 \)[/tex]:
[tex]\[ g(h(0)) = 6(0) - 5 = -5 \][/tex]
Therefore, the composite function [tex]\( g(h(t)) \)[/tex] simplifies to [tex]\( 6t - 5 \)[/tex]. For [tex]\( t = 0 \)[/tex], [tex]\( g(h(0)) = -5 \)[/tex].
### Step 1: Understand the Functions
Given the functions:
[tex]\[ g(t) = 2t + 3 \][/tex]
[tex]\[ h(t) = 3t - 4 \][/tex]
### Step 2: Substitute [tex]\( h(t) \)[/tex] into [tex]\( g \)[/tex]
We need to find [tex]\( g(h(t)) \)[/tex]. This means we will substitute the function [tex]\( h(t) \)[/tex] into the function [tex]\( g(t) \)[/tex].
### Step 3: Substitute [tex]\( h(t) \)[/tex] into [tex]\( g(t) \)[/tex]
First, we rewrite [tex]\( g(t) \)[/tex] so that it accepts [tex]\( h(t) \)[/tex]:
[tex]\[ g(t) = 2t + 3 \][/tex]
When substituting [tex]\( h(t) \)[/tex], we replace [tex]\( t \)[/tex] in [tex]\( g(t) \)[/tex] with [tex]\( h(t) \)[/tex]:
[tex]\[ g(h(t)) = g(3t - 4) \][/tex]
### Step 4: Evaluate [tex]\( g(3t - 4) \)[/tex]
Now, substitute [tex]\( 3t - 4 \)[/tex] wherever there is a [tex]\( t \)[/tex] in the function [tex]\( g(t) \)[/tex]:
[tex]\[ g(3t - 4) = 2(3t - 4) + 3 \][/tex]
### Step 5: Simplify the Expression
Next, we simplify the expression step-by-step:
[tex]\[ 2(3t - 4) + 3 \][/tex]
[tex]\[ = 2 \cdot 3t - 2 \cdot 4 + 3 \][/tex]
[tex]\[ = 6t - 8 + 3 \][/tex]
[tex]\[ = 6t - 5 \][/tex]
So, [tex]\( g(h(t)) = 6t - 5 \)[/tex].
### Final Answer:
To find the specific value of [tex]\( g(h(t)) \)[/tex] for a particular [tex]\( t \)[/tex], you would substitute the value of [tex]\( t \)[/tex] into [tex]\( 6t - 5 \)[/tex]. For example, if [tex]\( t = 0 \)[/tex]:
[tex]\[ g(h(0)) = 6(0) - 5 = -5 \][/tex]
Therefore, the composite function [tex]\( g(h(t)) \)[/tex] simplifies to [tex]\( 6t - 5 \)[/tex]. For [tex]\( t = 0 \)[/tex], [tex]\( g(h(0)) = -5 \)[/tex].
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.